IMPLIKASI PROSES PEMBELAJARAN TEMATIK KELAS V DI MADRASAH IBTIDAIYAH - Yuliani, Dewi; Rizqiani, Eni; Jannah, Nurul; Fatchurohman; Kamal, Rahmat (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Education plays an important role in shaping individual character and abilities. Thematic learning, which combines several subjects under one theme, is increasingly popular. This research explores the implications of thematic learning in grade 5 of SD Wonorejo, Pekalongan Regency. The aim of this research is to describe the implications of class V thematic learning at MI Salafiyah Wonorejo. This research method uses descriptive qualitative, data collection through observation, interviews and documentation. The research results explain that thematic learning environments are carried out both inside and outside the classroom. Thematic learning uses varied learning. This varied learning is adapted to student characteristics. Thematic learning as an integration approach naturally connects facts and ideas in an effort to understand the world. Through a theme network, students can connect ideas with experiences and the environment where students live. The implications of thematic learning include teacher creativity, active student participation, and the use of integrated textbooks. This research is relevant for improving the quality of education by designing more effective learning strategies.